Concise dictionary of mathematics - Clapham, Christopher (New York Oxford university press, 1996)
This dictionary contains over 3,000 clear and concise entries updated in line with curriculum and degree requirements. It covers pure and applied mathematics and statistics, features entry-level web links, and includes detailed appendices.
Keywords: Oxford mathematics dictionaries